ANALISIS KARAKTERISTIK HUNIAN UNTUK PASANGAN MUDA DI KOTA SURABAYA - Martha Jaya, Nyoman; Dharmayanti, GAP. Candra; Kharisma, Radhika (JURNAL SPEKTRAN, 2018)
Surabaya as the second largest metropolitan city in Indonesia after Jakarta has a population of 2,864,471 people.High Economic growth and business in the city of Surabaya have an influence on the demand for housing and land so that property prices in the Surabaya area increased 25-30 percent annually. Young couples who just got married at a relatively young age and have not been classified as a well-established couple need place to stay, but problemscan arise if they expect a proper residence in the city of Surabaya. This study aims to determine the priority of factors that affect young couples in choosing a residence, so that they have to knowthe concept of residence expected by a young couple in the cityof Surabaya. Based on the literature, factors identified include: building area, land area, accessibility, physical and environmental criteria, facilities and residential services, home price, type of work, and the amount of income.This study used a survey method using questionnaires distributed to 30 respondents with expert criteria,i.e. those who have been experienced or skilled in the area. Preference measurement is done by pair-wise comparisonsof factors that affectyoung couple choosing residential follows the rating principle of Saaty (1986). Data analysis methods used Analytic Hierarchy Process (AHP) and Fuzzy Analytic Hierarchy Process (FAHP)to obtain the priority factors influencing young couple in the city of Surabayafor choosing the residence.The results showed that the concept of residence expected by young couple in the city of Surabaya is influenced by factors such as the following, which are ranked from the most dominant by weight: land area factors(21.7%),accessibility factors (18.8%), physical characteristic and residential environmental factors(17.6%), facility and residential service (13.5%),factor in home prices (8.9%), factor of building area (8.8%), factors of income level (7.0%), factor of the type ofwork(3,7 %). Keywords : AHP,  FAHP, residential characteristic  factors, young couples